An economic study of the City of London - Economists Advisory Group; Dunning, John H.; Morgan, E. Victor; Corporation of London (England). (London : Allen & Unwin, 1971)
This was the first comprehensive study of the City of London to be published. The study examines the economic structure of the city and considers the main influences likely to affect the development of the City, including the pattern of demand, technological change, population movements, supply of labour and land values. Particular attention is paid to the City's international role. Specific chapters are devoted to Banking & Finance, Insurance, Trade, Commerce and the Port, and the Manufacturing Industry. The book is supported with a wealth of statistical material based on orig.
Commissioned by the Common Council of the City of London.
Includes bibliographical references.
aia 27/9/17
Loans
Keywords: Economic conditions; London